2017
DOI: 10.1007/s00705-017-3331-3
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective investigation and evolutionary analysis of a novel porcine deltacoronavirus strain detected in Thailand from 2008 to 2015

Abstract: Porcine deltacoronavirus (PDCoV) in Thailand was first detected in 2015. We performed a retrospective investigation of the presence of PDCoV in intestinal samples collected from piglets with diarrhea in Thailand from 2008 to 2015 using RT-PCR. PDCoV was found to be present as early as February 2013. Phylogenetic analysis demonstrated that all PDCoV variants from Thailand differ from those from other countries and belong to a novel group of PDCoV that is separate from the US and Chinese PDCoV variants. Evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…In the phylogenetic analysis, most of the global PDCoV strains could be divided into three lineages: the China lineage, the USA/Japan/South Korea lineage and the Viet Nam/Laos/Thailand lineage, this is consistent with previous reports (Lorsirigool et al, 2016;Saeng-Chuto et al, 2017b). Three sequenced strains (CH-HA1, CH-HA2 and CH-HA3), which formed a new monophyletic branch, were most closely related to the Viet Nam/Laos/Thailand lineage strains.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the phylogenetic analysis, most of the global PDCoV strains could be divided into three lineages: the China lineage, the USA/Japan/South Korea lineage and the Viet Nam/Laos/Thailand lineage, this is consistent with previous reports (Lorsirigool et al, 2016;Saeng-Chuto et al, 2017b). Three sequenced strains (CH-HA1, CH-HA2 and CH-HA3), which formed a new monophyletic branch, were most closely related to the Viet Nam/Laos/Thailand lineage strains.…”
Section: Discussionsupporting
confidence: 89%
“…Several genetic and phylogenetic analyses using S genes or complete genomes have indicated that the global PDCoV strains separated clearly into three lineages: the China lineage, the USA/Japan/South Korea lineage and the Viet Nam/Laos/Thailand lineage (Mai et al, 2018;Saeng-Chuto et al, 2017b;Suzuki et al, 2018). In the present study, to further investigate the epidemiology and phylogenetics of PDCoV in China, a total of 719 porcine samples from 18 provinces in China from 2016 to 2018 were simultaneously tested for PDCoV and PEDV.…”
Section: Introductionmentioning
confidence: 91%
“…In our present study, we found that the prevalences of PDCoV, PEDV and PDCoV + PEDV in Tibetan pigs were significantly lower than in pigs in other provinces of China (Dong et al., ; Song et al., ), South Korea (Jang, Lee, Kim, & Lee, ), Thailand (Janetanakit et al., ; Saeng‐Chuto et al., ) and the United States(Wang et al., ). The prevalence of PDCoV in Tibetan pigs was relatively low (3.70%), and only piglets were affected.…”
Section: Discussionmentioning
confidence: 44%
“…After the first report of PDCoV infection (Woo et al., ), its prevalence was detected in pigs in several states of the United States, South Korea, mainland China, Southern China and Thailand with majority of piglets having clinical diarrhoeal disease (Dong et al., ; Lee et al., ; Mai et al., ; Saeng‐Chuto et al., ; Wang et al., ). The prevalence of PDCoV in certain regions of the world is intriguing with regard to its epidemiology, evolution and pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…PDCoV infection is marked by acute, watery diarrhea and vomiting, ultimately leading to dehydration and mortality in suckling piglets Ma et al, 2015). Since its first discovery in Hong Kong in 2012 (Woo et al, 2012), this virus has emerged globally, especially in the North American and Asian pigproducing countries Madapong et al, 2016;Saeng-Chuto et al, 2017;Song et al, 2015;Wang et al, 2015;Woo et al, 2012;Li et al, 2014;Marthaler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%